The correlation between islamic mindfulness with nursing student professional attitude and caring behavior - Irma Nurbaeti; Kustati Budi Lestari; Tsal Tsa Khairunnisa (Jurnal Keperawatan Padjadjaran, 2024)
Background. Various stressors during the clinical practices may affect the psychological status of students which potentially impact on their professional attitudes and caring behavior. Prospective nursing students practices on clinical setting is necessary as the basis for strategy development in building students’ caring behavior. The role as care giver that believed can impact to professional attitude and caring behavior is Islamic mindfulness. The aim of the study was to identify the correlation between Islamic Mindfulness with professional attitude and caring behavior among nursing students. Methods. Cross-sectional design was carried out in this study. A total of 97 Moeslim students of nursing clinical Practices program were recruited from Islamic State University of Jakarta and Makassar Indonesia during November to December 2022 by total sampling.  Instruments of Islamic Mindfulness questionnaire, Caring Asessment Tool and Professional attitude for Nurses students were used.  Data collected by online. Bivariate analysis was performed to test the correlation between Islamic mindfulness with professional attitude and caring behavior among nursing students. Results. The mean score of Islamic mindfulness was 38.27 (SD=5.60), Professional attitude was 67.09 (SD=9.56) and Caring behavior was 84.96 (SD=15.14).  Islamic mindfulness had very week-positive correlation with professional attitudes but not significant (r=0.148; p-value= 0.073). Islamic mindfulness had a weak-positive and significant correlation with caring behavior (r=0.363; p-value= 0.0001).   Conclusion. Islamic mindfulness had a significant correlation to caring behavior. It is important to Nursing students features Islamic mindfulness to strengthen the caring behavior.